Critical analysis of current methods for assessing the in vitro antioxidant and antibacterial activity of plant extracts. (1st April 2015) - Tan, Joash Ban Lee; Lim, Yau Yan
Highlights: Discusses selection of optimal antioxidant/antibacterial assays. Discusses strengths and weaknesses of many common antioxidant/antibacterial assays. Highlights alternative assays. Abstract: Natural product research is an active branch of science, driven by the increased value placed on individual health and well-being. Many naturally-occurring phytochemicals in plants, fruits and vegetables have been reported to exhibit antioxidant and antibacterial activity; often touted as being beneficial for human health. In vitro screening is a common practice in many research laboratories as a means of rapidly assessing these properties. However, the methods used by many are not necessarily optimal; a result of poor standardization, redundant assays and/or outdated methodology. This review primarily aims to give a better understanding in the selection of in vitro assays, with emphasis placed on some common assays such as the total phenolic content assay, free radical scavenging activity, disc-diffusion and broth microdilution. This includes a discussion on the reasons for choosing a particular assay, its strengths and weaknesses, ways to improve the accuracy of results and alternative assays.